Igualdade de gênero tributária: contribuição para o debate sobre igualdade tributária e igualdade de gênero a partir dos direitos humanos - Thiago Álvares Feital (2022)
The accumulated literature from the last decades of the last century shows that tax systems can discriminate on the basis of gender. Based on this premise, the purpose of this study was to determine whether there is a provision in Brazilian law that establishes gender equality in the tax system, and if so, what obligations this provision imposes on the tax legislator. In the first part of this dissertation, starting from the Structuring Theory of Law, a theoretical framework that allows understanding the relationship between gender inequality and the textual provisions that command the realization of equality, the limitations of the theory of law and the characteristics that make gender inequality a wicked problem were analyzed. Then, the existing theories and data on gender inequality and economic inequality were examined to understand the phenomenon in the light of social sciences and philosophy, and the main controversies on equality were examined to understand how the theories that influence law relate to each other. In the second part, we analyzed the history of the debate on taxes and gender and the main points in the literature on personal income and consumption taxes. We then discussed the nature and meaning of the normative texts prescribing gender equality in CEDAW and examined the tax literature to identify the structuring elements of tax equality, concluding that CEDAW imposes obligations on the Brazilian tax legislature. In response to the research question, we argue that there is a tax gender equality rule in Brazilian law, a rule that is structured in three dimensions: formal, substantive and transformative. It has been shown that each of these dimensions is associated with certain institutes of tax law, namely transparency and nondiscrimination, economic ability and progressivity, and tax expenditures.